2012
DOI: 10.1021/es300234v
|View full text |Cite
|
Sign up to set email alerts
|

In Situ X-ray Diffraction Study of Na+ Saturated Montmorillonite Exposed to Variably Wet Super Critical CO2

Abstract: Reactions involving variably hydrated super critical CO(2) (scCO(2)) and a Na saturated dioctahedral smectite (Na-STX-1) were examined by in situ high-pressure X-ray diffraction at 50 °C and 90 bar, conditions that are relevant to long-term geologic storage of CO(2). Both hydration and dehydration reactions were rapid with appreciable reaction occurring in minutes and near steady state occurring within an hour. Hydration occurred stepwise as a function of increasing H(2)O in the system; 1W, 2W-3W, and >3W clay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
149
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(177 citation statements)
references
References 46 publications
28
149
0
Order By: Relevance
“…For example, the experimental studies conducted by Al Otaibi et al [93] and Giesting et al [94] showed that super-critical CO 2 adsorption into clay minerals (Na or Ca-montmorillonite in this case) does not produce any significant swelling in dry clay minerals. Maximum expansion caused by CO 2 from 11.3 Å to 12.3 Å occurred when small amounts of water present in montmorillonite and the swelling is nearly an order of magnitude lower than that caused by water [94,95]. While for clay minerals with high water saturation, the dehydration effect caused by CO 2 dominates the hydration effect and CO 2 also causes the net drying of clay particles, resulting in reduction of the basal spacing of swelled clay minerals.…”
Section: Avoidance Of Swelling-related Issuesmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, the experimental studies conducted by Al Otaibi et al [93] and Giesting et al [94] showed that super-critical CO 2 adsorption into clay minerals (Na or Ca-montmorillonite in this case) does not produce any significant swelling in dry clay minerals. Maximum expansion caused by CO 2 from 11.3 Å to 12.3 Å occurred when small amounts of water present in montmorillonite and the swelling is nearly an order of magnitude lower than that caused by water [94,95]. While for clay minerals with high water saturation, the dehydration effect caused by CO 2 dominates the hydration effect and CO 2 also causes the net drying of clay particles, resulting in reduction of the basal spacing of swelled clay minerals.…”
Section: Avoidance Of Swelling-related Issuesmentioning
confidence: 96%
“…While for clay minerals with high water saturation, the dehydration effect caused by CO 2 dominates the hydration effect and CO 2 also causes the net drying of clay particles, resulting in reduction of the basal spacing of swelled clay minerals. The D-spacing of Na-Montmorillonite with 64% water saturation collapsed by 15% after exposed to super-critical CO 2 [95] and Al Otaibi et al [93] found that the D-spacing of fully hydrated Na and Ca-montmorillonite decreased by a significant amount (around 25% and 14.2%) after super-critical CO 2 treatment.…”
Section: Avoidance Of Swelling-related Issuesmentioning
confidence: 99%
“…Data on the clays, mudrocks and siltstones from Amann et al (2011), Busch et al (2008, Jeon et al (2014); for the silica gels from Rother et al (2013b), and for the natural coals and activated carbon from Gensterblum et al (2009Gensterblum et al ( , 2010 when charged with CO 2 . Measurements were performed on smectite samples exchanged with different cations (K, Ca, Na) using X-ray diffraction (XRD) in an environmental chamber (Giesting et al 2012a, b;Ilton et al 2012;Schaef et al 2012). All measurements on pure clay samples discussed below used standard clays provided by the Source Clays Repository, the Clay Minerals Society, hosted at the Department of Geology, University of Missouri, Columbia, MO, and described in detail by Costanzo and Guggenheim (2001).…”
Section: Co 2 Sorption On Clay Mineralsmentioning
confidence: 99%
“…Desiccation of clays represents a potential mechanism for creation and/or exacerbation of permeable pathways in caprock, thus posing risk to storage integrity [18,41]. Schaef et al [42] and Ilton et al [43] point out potential drying and/or expansion of clay (i.e., low iron montmorillonite saturated with Na + or Ca…”
Section: Introductionmentioning
confidence: 99%
“…Injected, anhydrous CO 2 will dissolve water to solubility limits such that subsequent dry-out of clays by CO 2 near wellbores may occur. Ilton et al [43] and Schaef et al [42], using in situ high pressure X-ray diffraction (XRD), observed changes in smectite clay interlayer spacing upon exposure to CO 2 at variable water content, which suggests dehydration and potential shrinkage of caprock. In contrast, using Monte Carlo and molecular dynamics simulations, Botan et al [41] investigated interlayer spacing of smectite under varying amounts of water and CO 2 , but neither shrinkage nor swelling were observed.…”
Section: Introductionmentioning
confidence: 99%